Pioneers: First Women Filmmakers [2018] - Wood, Bret; Stamp, Shelley (New York : Kino Lorber, 2018)
Baldwin, Ruth Ann / Cunard, Grace / Reid, Dorothy Davenport / Guy-Blaché, Alice / Hurston, Zora Neala / Madison, Cleo / Marion, Frances / Nazimova, Alla / Normand, Mabel / Park, Ida May / Shipman, Nell / Weber, Lois / Wilson, Elsie Jane / Wong, Marion E. / Holmes, Helen / Gibson, Angela Murray / Warrenton, Lule / Ivers, Julia Crawford
booklet
film